Enhancement of Learning through Collaborative Learning Techniques - Mehar, Ram; Kaur, Prabhjit (International Journal of Psychosocial Rehabilitation, 2024)
he present paper examines the role of collaborative learning techniques in enhancing the learning of students .Collaborative learning is the educational approach of using groups to enhance learning through working together. The two groups or more learners work together to solve problems, complete tasks, or learn new concepts. This approach actively engages learners to process and synthesize information and concepts, rather than using rote memorization of facts and figures. In the paper types of collaborative learning have also been discussed. Various studies supported engagement of collaborative learning in improving learning has also given. The result of experiment conducted has shown that the collaborative learning significantly enhances the learning in of students and students prefer to work in groups to learn effectively